Long-term survival in multiple myeloma. - João, C (2015)
KEY CLINICAL MESSAGE: The survival of multiple myeloma patients has improved very significantly over the last decade. Still median overall survival is inferior to 5 years. A small proportion of patients survive longer than 10 years. In this paper we discuss four cases illustrating the nonhomogeneous clinical presentation and evolution of this subset of patients. Surprisingly, these long survivors do not always have deep responses and some require frequent treatments, which include autologous stem cell transplantation and novel drugs. The authors discuss several aspects of these clinical histories, including treatment options, raising hypothesis on their relation with long survivorship which may be important to have in consideration when studying this subject.